The XMM cluster outskirts project (X‐COP). Issue 2 (27th April 2017) - Eckert, D.; Ettori, S.; Pointecouteau, E.; Molendi, S.; Paltani, S.; Tchernin, C.; ,
Abstract : Galaxy clusters are thought to grow hierarchically through the continuous merging and accretion of smaller structures across cosmic time. In the local universe, these phenomena are still active in the outer regions of massive clusters ( R > R 500 ), where the matter distribution is expected to become clumpy and asymmetric because of the presence of accreting structures. We present the XMM‐Newton cluster outskirts project (X‐COP), which targets the outer regions of a sample of 13 massive clusters ( M 500 > 3 × 10 14 M ⊙ ) in the redshift range 0.04–0.1 at uniform depth. The sample was selected based on the signal‐to‐noise ratio in the Planck Sunyaev–Zeldovich (SZ) survey with the aim of combining high‐quality X‐ray and SZ constraints throughout the entire cluster volume. Our observing strategy allows us to reach a sensitivity of 3 × 10 − 16 ergs cm − 1 s − 1 arcmin − 2 in the 0.5–2.0 keV range thanks to a good control of systematic uncertainties. The combination of depth and field of view achieved in X‐COP will allow us to pursue the following main goals: (a) measure the distribution of entropy and thermal energy to an unprecedented level of precision; (b) assess the presence of nonthermal pressure support in cluster outskirts; and (c) study the occurrence and mass distribution of infalling gas clumps. We illustrate the capabilities of the program with a pilot study on the cluster Abell 2142.